Facilitators, barriers and recommendations on the use of Information and Communication Technologies by adults with cerebral palsy in Brazil - Curioso-Vílchez, Iván Carlos [UNESP] (AISTI, 2021)
The use of Information and Communication Technologies (ICTs) by people with physical disabilities, including adults with cerebral palsy, presents research gaps. The present work aims to identify the facilitators, barriers and recommendations of the use of traditional computer, notebook, smartphone and tablet, by adults with cerebral palsy in Brazil. For this purpose, twelve semi-structured interviews were conducted with people with this condition who lived south of the State of São Paulo. The opportunities or benefits of the use of ICTs are indicated as facilitators. The difficulties due to the physical limitations and different functionalities of ICTs are expressed as barriers. Finally, recommendations for improving the accessibility and the use of ICTs for this population are highlighted. In conclusion, the use of ICTs is a fundamental tool for the people with cerebral palsy interviewed.
Facilitadores, barreras y recomendaciones sobre el uso de las Tecnologías Digitales de la Información y la Comunicación por adultos con parálisis cerebral en Brasil
Keywords: Barriers; Cerebral Palsy; Facilitators; Information and Communication Technologies; Recommendations